Investigating the Influence of E-Marketplace Usage, and E-Commerce Benefits on Supply Chain Management in Pakistani Industries - Rehmat, Sana; Islam, Madeeha; Khan, Asma (Archives of Business Research, 2022)
Today’s business environment changed drastically due to rapid growth in communication and information technologies, leading to the emergence of electronic commerce among the top companies. It has been recognized that simple ideas are becoming more evolutionary due to exponential changes in e-commerce. Hence, the purpose of this research is to determine the direct impact of e-marketplace usage and e-commerce benefits on supply chain management. Data was collected from those companies enlisted in the Lahore Chamber of Commerce and Industry and using e-commerce. Factor analyses, mediating regression, correlations, and descriptive analyses and were employed. The study results suggested that e-marketplace usage and e-commerce benefits had a direct and positive impact on supply chain management. The results also proved the mediating role of e-marketplace usage among e-commerce and supply chain management relationships. The implications for strategic level management and limitations for future researchers were discussed hereunder.